I. Barreñada (Coord.) (2018). Entre España y Palestina. Revisión crítica de unas relaciones. Madrid: Bellaterra. 327 pp. - Ignacio Gutiérrez de Terán Gómez-Benita (El Colegio de México, A.C., 2020)
I. Barreñada (Coord.) (2018). Entre España y Palestina. Revisión crítica de unas relaciones. Madrid: Bellaterra. 327 pp.